Re-viewing Foucault: The Disciplinary Gaze in Harun Farocki’s I Thought I Was Seeing Convicts, Lockup 360 and Fiona Tan’s Correction - Martine Beugnet (Transatlantica)
Has the Panopticon, as a scholarly and artistic model, definitively lost its topicality and pertinence? Has it become a mere shorthand, used to designate the study and representation of power-knowledge relations that have moved well beyond both the realities and theorizations it once stood for, including Michel Foucault’s analysis of it? This article proposes to take a fresh look at the legacy of Michel Foucault’s Discipline and Punish: The Birth of the Prison, focusing on documentary works that take the American prison system as their topic. In the video installations and televisual production concerned, the acknowledgement of the failure of the “ideal” model evoked by Foucault with reference to the Panopticon and the establishment of a perverted system of pure control lead to an interrogation of contemporary forms of spectatorial engagement.